ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022) - Lutfi, Aulia; Winarko, Sigit Puji; Sugeng, Sugeng (Universitas Nusantara PGRI Kediri, 2023)
This study looked at the impact of public accounting firm size, time budget pressure, and audit tenure on the quality of audits performed on mining companies that were partially or concurrently listed on the IDX in 2020-2022. Ex post facto methodology and a quantitative technique were both used in this investigation. 32 mining companies listed on the IDX in 2020–2022 made up the samples used in this study, which used logistic regression tests and SPSS 22 for Windows for analysis. According to the study's findings, the size of the public accounting firm, time constraints, and audit tenure do not significantly affect the audit quality of mining companies that are listed on the IDX in 2020–2022.